The relationship between perceived stress and bedtime procrastination among Chinese college students: a moderated mediation model - He, Qiuyue; Wu, Huiyi; Meng, Xiaolu; Li, Chunlu (Frontiers in Psychiatry, 2025)
Introductionthe role of stress in inducing bedtime procrastination is a new research topic that has emerged in recent years. This study aimed to explore the psychological mechanism by which perceived stress affects bedtime procrastination in Chinese college students in a life history framework.Methodsfirst, we investigated whether life history strategy mediate their relationships. Then, we examined whether distress tolerance moderated the direct effects of perceived stress on bedtime procrastination and/or the indirect effects of them mediated by life history strategy. The data of 1021 college students were analyzed.Resultsthe results showed that: (1) perceived stress had a significant predictive effect on bedtime procrastination; (2) life history strategy played a mediating role in the relationship between perceived stress and bedtime procrastination; (3) distress tolerance moderated the indirect effect between them mediated by life history strategy, but not the direct effect between them.Discussionthe present study suggested that life history-based interventions might be an effective intervention for stress-induced bedtime procrastination. Specifically, it might be helpful for alleviation of bedtime procrastination to develop slow life history strategy, when faced with similar stressful situations in the future. Furthermore, distress tolerance may be an important alternative target.